2022
DOI: 10.1002/srin.202200556
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and Kinetic Analyses of Inclusion Transformations in Linepipe Steel during Isothermal Heating at 1473 K (1200 °C)

Abstract: Understanding the thermodynamics and kinetics of solid‐state reactions on the characteristic transformations of nonmetallic inclusions in the linepipe steel during isothermal heating is of great importance for achieving good steel quality. Herein, heat treatment experiments are used, which are carried out at 1473 K (1200 °C) between 1 and 10 h in an Ar atmosphere, to investigate the resulting changes in the inclusion characteristics of linepipe steel. The chemical compositions, morphology, and size distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Chu et al [4] found a similar reaction during heat treatment of linepipe steels in the temperature range of 1000-1400 • C. Wang et al [5] developed a kinetic model for the reactions involving MgO-Al 2 O 3 -CaO-CaS components and the steel matrix, constructing Time-Diameter-Transformation contours to assess the NMI composition over heating time. Liu & Webler [6,7] reported on the reactions of dissolved Mn with CaS in inclusions, promoting the formation of a solid solution (Ca, Mn)S phase in CaS and MgO-Al 2 O 3 -CaO(-CaS) type NMIs. Until recently, there was a lack of insitu observation of solid-state NMI reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Chu et al [4] found a similar reaction during heat treatment of linepipe steels in the temperature range of 1000-1400 • C. Wang et al [5] developed a kinetic model for the reactions involving MgO-Al 2 O 3 -CaO-CaS components and the steel matrix, constructing Time-Diameter-Transformation contours to assess the NMI composition over heating time. Liu & Webler [6,7] reported on the reactions of dissolved Mn with CaS in inclusions, promoting the formation of a solid solution (Ca, Mn)S phase in CaS and MgO-Al 2 O 3 -CaO(-CaS) type NMIs. Until recently, there was a lack of insitu observation of solid-state NMI reactions.…”
Section: Introductionmentioning
confidence: 99%